Assessment of Thrombin Inhibitor Efficacy in a Novel Rabbit Model of Simultaneous Arterial and Venous Thrombosis - Lyle, Elizabeth Marsh; Lewis, Sidney D.; Lehman, Dale E.; Gardell, Stephen J.; Motzel, Sherri L.; Lynch, Joseph J., Jr. (Thrombosis and Haemostasis, 1998)
The importance of thrombin in arterial and venous thrombosis renders thrombin inhibition an important therapeutic target. Identification of novel inhibitors requires an appropriate animal model. We modified a previously reported rat arterial thrombosis model to allow simultaneous assessment of the arterial and venous antithrombotic efficacies of heparin, hirudin, hirulog, a novel thrombin inhibitor H-(N-Me-D-Phe)-Pro-L-trans-4-aminocyclohexyl-Gly-[CO-CO]-NHCH3 (L-370,518) and the factor Xa inhibitor tick anticoagulant peptide in rabbits. Thrombosis was induced through application of 70% ferric chloride to the femoral artery and jugular vein. Incidence of occlusion, thrombus weight, aPTT and plasma inhibitor concentrations were determined. Heparin was efficacious in preventing arterial and venous occlusive thrombosis but at a dose that profoundly elevated aPTT. On a molar dosing basis, the approximate order of potency of the thrombin and factor Xa inhibitors was similar in artery and vein: hirudin>tick anticoagulant peptide>hirulog≥L-370,518. Data suggested that compounds tended to be more potent in preventing venous thrombosis than arterial. This thrombin-dependent model is an economical and efficient approach to arterial and venous antithrombotic efficacy screening that eliminates variabilities encountered when multiple model/multiple animal strategies are employed.